Review of sustainable strategies for the use of organic waste in organizations - Alvarado Dávila, Tatiana Liceth; Rangel Zambrano, Shirley Andrea (Revista Colombiana de Investigaciones Agroindustriales, 2021)
Solid organic waste, produced by various agricultural, forestry, industrial, commercial and domestic activities, constitutes a significant volume over the total waste generated, because of that, it is essential to look for a comprehensive outlet that contributes to the use and reduction of environmental impacts. In Colombia, the use of organic solid waste emphasize in composting, defined as the process of decomposition of organic waste by microbial action, changing its molecular structure. In order to achieve a quality product such as compost, it is necessary to comply with the parameters that guarantee better conditioning of the soils, the supply of nutrients for the plants, humidity conditions, pH, temperature, organic matter, and organic carbon; in order to optimize the biological activity of the soil to guarantee a good final production. In this research study, it was determined to carry out the bibliographic review about the transformation of organic waste where some experiences at a global, regional and local level analyse various treatments, the positive and negative impacts presented, the use, commercialization, and financial viability costs for the composting of organic fertilizers. It was clear that the implementation of an organic fertilizer production plant for the elaboration, production and commercialization of compost is feasible for start-ups and has good acceptance by farmers and peasants, where necessary resources such as raw material, labour, the assembly site of the plant must be considered, as it contributes to the achievement of an eco-sustainable market for the environment.